PENERAPAN TEORI DIENES MELALUI PERMAINAN TRADISIONAL BANDARAN UNTUK MENINGKATKAN KEMAMPUAN MENGHITUNG PERKALIAN SISWA KELAS 2 SDN TANJUNGSARI 1 KOTA BLITAR - Eriyatmoko, Sapta (Jurnal Pembelajaran Matematika, 2017)
The purpose of this study was to describe the application of the theory a Dienes through traditional games bandaran to improve calculate multiplication. This study used a qualitative approach to the type of classroom action research (PTK), which consists of two cycles, each cycle consisting of three meetings. Subjects in the study were students in grade 2 SDN Tanjungsari 1 Kota Blitar totaling 27 students. In collecting the data, researchers using observation, interviews, tests, and documentation. The results showed an increase in activity of the teacher in the first cycle of 76% and cycle II of 92.5%. Increased activity of students also increased from the first cycle of 73.65% and 85.45% second cycle. And the results of this study showed a significant improvement of learning outcomes classical completeness of 11.11 from before action is taken by looking at the average daily tests carried out before and after the final test cycle 1. The student learning outcomes of the first cycle has increased by 9, 82 to cycle 2. Based on these results, it can be concluded that the application of the theory through traditional games bandaran Dienes done in the subjects of Mathematics 2nd grade at SDN Tanjungsari 1 can improve numeracy skills and student learning outcomes.